2015
DOI: 10.4236/jmp.2015.613197
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Phase Portraits for the Study of the Generation-Recombination Processes in Semiconductor

Abstract: Theoretical investigation of generation-recombination processes in silicon, which has a lifetime of charge carriers 10 −3 s and capture cross sections of 10 −16 sm 2 . For the study uses a method of phase portraits, which are widely used in the theory of vibrations. It is shown that the form of phase portraits strongly depends on the frequency of exposure to the external variable deformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…As is known, when calculating integral (11), as a result of the change of variables, the integrand is transformed into a delta function, the effective density of states is transformed into…”
Section: Model Of the Thermodynamic Density Of Surface States Materiamentioning
confidence: 99%
See 2 more Smart Citations
“…As is known, when calculating integral (11), as a result of the change of variables, the integrand is transformed into a delta function, the effective density of states is transformed into…”
Section: Model Of the Thermodynamic Density Of Surface States Materiamentioning
confidence: 99%
“…Using formula (23), one can calculate the density of energy states in a wide energy range, including the valence band, the forbidden band, and the conduction band. A feature of the model is the preservation of the temperature dependence of statistical functions, which help determine the contribution of thermal broadening to the spectrum of the density of energy states [11]. The proposed method allows one to determine discrete energy levels created by impurities with greater accuracy over a wide energy range.…”
Section: Model Of the Thermodynamic Density Of Surface States Materiamentioning
confidence: 99%
See 1 more Smart Citation
“…For analysis of oscillatory processes, phase portraits (PhP) are used effectively, because they give the most complete picture of what is happening. In [4] using PhP the influence of frequency of variable deformation on the concentration of charge carriers in semiconductor illuminated by its forbidden zone's light, it is shown that the frequency of the variable deformation has a strong influence on the shape of the PhP. However, in [4] influence of recombination centers in the form of PhP is not investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In [4] using PhP the influence of frequency of variable deformation on the concentration of charge carriers in semiconductor illuminated by its forbidden zone's light, it is shown that the frequency of the variable deformation has a strong influence on the shape of the PhP. However, in [4] influence of recombination centers in the form of PhP is not investigated. In this paper, we investigate influence of the change of recombination centers in the semiconductor by PhP.…”
Section: Introductionmentioning
confidence: 99%